PSMA expression in the Hi‐Myc model; extended utility of a representative model of prostate adenocarcinoma for biological insight and as a drug discovery tool. Issue 6 (17th January 2019) - Simons, Brian W.; Turtle, Norman F.; Ulmert, David H.; Abou, Diane S.; Thorek, Daniel L. J.
Abstract : Prostate‐specific membrane antigen (PSMA), also known as glutamate carboxypeptidase II (GCPII), is highly overexpressed in primary and metastatic prostate cancer (PCa). This has led to the development of radiopharmaceuticals for targeted imaging and therapy under current clinical evaluation. Despite this progress, the exact biological role of the protein in prostate cancer development and progression has not been fully elucidated. This is in part because the human PSMA and mouse PSMA (mPSMA) have different patterns of anatomical expression which confound study in the most widely utilized model organisms. Most notably, mPSMA is not expressed in the healthy murine prostate. Here, we reveal that mPSMA is highly upregulated in the prostate adenocarcinoma of the spontaneous Hi‐Myc mouse model, a highly accurate and well characterized mouse model of prostate cancer development. Antibody detection and molecular imaging tools are used to confirm that mPSMA is expressed from early prostatic intraepithelial neoplasia (PIN) through adenocarcinoma.